Consumer attitudes and perceptions towards Western cuisine: a strategic investigation of the Italian restaurant industry in Malaysia - Camillo, Angelo; Abdul Karim, Muhammad Shahrim (Taylor & Francis, 2014)
This study investigates consumer attitudes towards Italian cuisine in Malaysia. The popularity of Italian cuisine continues to shape the global evolution of Western-ethnic cuisines. Simplicity, taste, and food preparation of Italian cuisine stimulates new restaurant creation. This study uses in-depth analysis of research literature together with a strategic environmental scan and structured interviews. The results show that high prices, doubts regarding authenticity, and Muslim concerns regarding pork dishes create uncertainty among Malaysian consumers. These negative perceptions could dampen growth in the Italian cuisine sector. The study contributes to strategic marketing, entrepreneurship, and tourism related studies and practitioners in the field.